2018
DOI: 10.1007/s00268-018-4597-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Preoperative Systemic Inflammation Score in Short‐Term and Long‐Term Outcomes of Patients with Pathological T2–4 Gastric Cancer After Radical Gastrectomy

Abstract: SIS represents a simple predictor for incidence of postoperative complications and survival in patients with pT2-4 GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…Recently, Sato et al also found that SIS can predict the survival in a small cohort of patients with pT2-4 GC after radical gastrectomy, and they found that the SIS was not an independent prognostic factor, [32] this finding was consistent with the current study. Compared with the study of Sato, our study has the following advantages.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Sato et al also found that SIS can predict the survival in a small cohort of patients with pT2-4 GC after radical gastrectomy, and they found that the SIS was not an independent prognostic factor, [32] this finding was consistent with the current study. Compared with the study of Sato, our study has the following advantages.…”
Section: Discussionsupporting
confidence: 92%
“…An additional explanation could be that delayed administration after 8 weeks was associated with several factors that are related to hematogenous recurrence. Age, total gastrectomy, disease stage, and postoperative complications are reported to correlate with malnutrition and pro-inflammatory status, and poor status of these is related to hematogenous recurrence of gastric cancer [22]. In our study, most of these factors also caused a delay in the initiation of S-1 monotherapy.…”
Section: Discussionmentioning
confidence: 49%
“…SIS is based on the serum albumin level and the lymphocyte-to-monocyte ratio and is scored simply as 0, 1, and 2 [50]. Sato et al investigated the relationship between preoperative SIS and postoperative complications in 187 previously untreated patients who underwent gastrectomy for pT2-4 gastric cancer and found a significant positive association between the SIS score and the incidence of complications [51]. One explanation for this is that a decreased lymphocyte count can compromise antimicrobial immune responses, contributing to increased infection with bacteria and other potential pathogens [50,52].…”
Section: Inflammationmentioning
confidence: 99%